CHEMICAL COMPOSITION OF SOLID MINERALS FROM LOKOJA AND JOS IN NORTH CENTRAL NIGERIA (FULafia Journal of Science and Technology, 2017)
The structural, qualitative and quantitative analysis of grained rock samples were carried out with the view to establishing the mineral components present in the samples. Two samples were collectedfrom a mining site in Jos, Plateau State as well as from another mining site in Lokoja, Kogi State.The two samples were prepared for XRD analysis using a backloading preparation method and done with X-ray diffractometer. The analysis confirmed the presence of minerals such as Cassiterite (SnO2), Ilmenite (FeTiO3), Zircon (SiO4),Columbite (Fe), Manganoan in the ample from Jos as a result of the matching of the peaks with the database 2θ values. The percentage area integration of the various phases which correlated to the quantity of the various minerals in the sample revealed that Cassiterite(Tin Oxide) of 65.9% value was from Jos and is a Tin Ore. The grain sizes for Cassiterite (SnO2), Ilmenite (FeTiO3), Zircon (SiO4), Columbite (Fe), Manganoan are 17.674, 35.348, 37.208, 70.695, 20.199 in nm respectively. The samples from Lokoja showed the presence of Magnetite (Fe¬3O4), Quartz (SiO2), Hematite (Fe2O3) and Geothite(FeO(OH)) and confirmed the grain sizes of 28.278, 35.348, 28.278. 17.673 and 23.565 in nm respectively.The constituents of Lokoja samples, all of which contained Iron Oxide also indicate that the sample is an Iron Ore. These findings confirm the fact that the mineral resources that are present in these regions of the country areeconomically viable and have the potential to boost economy and industrial development